Childhood Septicemia in Tripoli, Libya: Bacterial Etiology and Its Antibiotic-Resistant Pattern - Heba Abuhelala; Asma Elkammoshi; Abir Ben Ashur; Hiba Alsharif; Atia, Ahmed (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Septicemia is a frequently occurring illness, but it affects children, particularly newborns and young infants, more than any other age group. This study aimed to determine the prevalence of septicemia in children and their antibiotic resistance pattern. Methods. A retrospective cross-sectional study was carried out during the period from April 2021 to July 2022 on a total of 302 patients who attended different polyclinics in Tripoli, Libya. Results. Out of 302 blood cultures, only 60 (19.8%) were positive growth of bacteria. Gram-positive bacteria constituted 32(53.3%) while Gram-negative bacteria were 28(46.7%). The highest number of isolates were Klebsiella pneumoniae (28.3%) followed by Staphylococcus aureus (20.0%), Staphylococcus epidermidis (15.0%), Staphylococcus haemolyticus (10.0%). While, in E. coli (10.0%), Pseudomonas aeruginosa, enterococcus faecalis were the most frequent isolates (5%, each), followed by Streptococcus ssp., (3.33%), Acinetobacter baumanii (1.66%), and Burkholderia cepacia (1.66%). Most of isolates were resistant to the commonly used antibiotics such as gentamicin, erythromycin, and ticarcillin. Overall, the majority of isolates were multidrug resistant. Conclusion. The study has brought attention to the significant impact of bacterial infection as a cause of septicemia in children at a healthcare facility in Tripoli.